Wiskott-Aldrich Syndrome: Description of a New Gene Mutation With Normal Platelet Volume. Issue 7 (October 2015) - Yoonessi, Leila; Randhawa, Inderpal; Nussbaum, Eliezer; Saharti, Samah; Do, Paul; Chin, Terry; Zwerdling, Ted
Abstract : Wiskott-Aldrich syndrome (WAS) is a rare X-linked primary immunodeficiency characterized by an increased incidence of autoimmunity, malignancy, microthrombocytes with thrombocytopenia, eczema, and recurrent infections. In this case report, we present a novel mutation, hemizygous for c.1125_1129delTGGAC mutation in the WAS gene, and a unique clinical presentation. Our patient was initially diagnosed with a milk protein allergy after presenting with a lower gastrointestinal bleed, leukopenia, and thrombocytopenia with normal platelet volume. However, signs of vasculitis and detection of microthrombocytes required additional testing and consideration of WAS. This case report illustrates the importance of retaining a high index of clinical suspicion despite normal platelet volume, as well as adding to the growing number of known mutations associated with WAS.